2017
DOI: 10.1080/10872981.2017.1396174
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the merits of a mandatory large group classroom learning format: an MD-MBA perspective

Abstract: The role of classroom learning in medical education is rapidly changing. To promote active learning and reduce student stress, medical schools have adopted policies such as pass/fail curriculums and recorded lectures. These policies along with the rising importance of the USMLE (United States Medical Licensing Examination) exams have made asynchronous learning popular to the detriment of classroom learning. In contrast to this model, modern day business schools employ mandatory large group classes with assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…More specifically, experiential learning for leadership development can take many forms, for example, engaging in play (Kark, 2011), participating in reflection and personal development (Petriglieri et al, 2011), and challenging managerial assignments (Day & Dragoni, 2015). Research has found learning through experience to be related to the development of both critical leadership competencies, such as cultural intelligence (Li & Pinto-Powell, 2017), and to provide a valuable vehicle for preparing oneself for future leadership challenges such as those related to sustainability (Gitsham, 2012).…”
Section: The Value Of Experiential Learning For Developing Leadership Competenciesmentioning
confidence: 99%
“…More specifically, experiential learning for leadership development can take many forms, for example, engaging in play (Kark, 2011), participating in reflection and personal development (Petriglieri et al, 2011), and challenging managerial assignments (Day & Dragoni, 2015). Research has found learning through experience to be related to the development of both critical leadership competencies, such as cultural intelligence (Li & Pinto-Powell, 2017), and to provide a valuable vehicle for preparing oneself for future leadership challenges such as those related to sustainability (Gitsham, 2012).…”
Section: The Value Of Experiential Learning For Developing Leadership Competenciesmentioning
confidence: 99%
“…Key thinkers on critically reflexive teaching practice often discuss engaged pedagogy as something that can best happen in small group contexts. Some research has demonstrated that being enrolled in a large class can have an impact on educational attainment as a result of being precluded from receiving formative feedback (Broadbent, Panadero, & Boud, 2018; Nicol, 2007), asking for help and engaging in discussions between faculty research experts (Asikainen, Virtanen, Postareff, & Heino, 2014; Karabenick, 2003; Li & Pinto-Powell, 2017; Woollacott, Booth, & Cameron, 2014).…”
Section: Overviewmentioning
confidence: 99%
“…When there are too many students, instructors cannot pay individual attention to each of them, and have to use teaching and assessment methods that can be scaled up. As such, this practical choice often results in the less frequent use of learner-centered activities in large classes (Asikainen et al, 2014; Isbell & Cote, 2009; Karabenick, 2003; Li & Pinto-Powell, 2017; Nicol, 2007; Woollacott et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For reference, in a typical class in management and organizational behavior, more than 50 or 60 students could be considered large (e.g., Exeter et al, 2010; Heaslip et al, 2014). Much research has identified teaching and attending large classes as being considered of lower quality and less effective compared with small classes (Asikainen et al, 2014; Boland, 2011; Broadbent et al, 2018; Inge & Bhardwa, 2018; Isbell & Cote, 2009; Karabenick, 2003; Li & Pinto-Powell, 2017; Nicol, 2007; Watts & Robertson, 2011; Woollacott et al, 2014). However, some have argued that instead of a characteristic or dynamic implicit to large classes, it is the skepticism about large classes, from both instructors and students, that generates a negative impact on student learning (Maxwell & Lopus, 1995; Sigfried & Walstad, 1998).…”
Section: Introductionmentioning
confidence: 99%